Literature, testimony, promise - Torralba, Concha (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper focuses on what happens when literature goes beyond itself and unfolds the aporias that constitute the notion of testimony and promise. Based on a deconstructive reading of the stories about the shootings in Viznar and in León mining basin in 1936, told by Mercedes del Amo and Josefina Aldecoa.
Keywords: testimony; promise; deconstruction; Mercedes del Amo; Josefina Aldecoa